The Complete Letters of Henry James, 1878-1880 : Volume 2 - James, Henry, 1843-1916 (Book collections on Project MUSE., 2015)
Containing letters written between September 2, 1879, and May 14, 1880, this second volume of The Complete Letters of Henry James, 1878-1880 documents the full establishment of Henry James as a professional writer and critic on both sides of the Atlantic, as James publishes the novel Confidence and the literary biography Hawthorne and begins work on Washington Square and The Portrait of a Lady. James also visits Paris, Florence, Rome, and Naples; begins his friendship with Constance Fenimore Woolson; and deepens his attachment to London and to his friends and acquaintances there.